Dapagliflozin Alleviates Hepatic Steatosis by Restoring Autophagy via the AMPK-mTOR Pathway - Li, Liuran; Li, Qinghua; Huang, Wenbin; Han, Yibing; Tan, Huiting; An, Min; Xiang, Qianru; Zhou, Rui; Yang, Li; Cheng, Yanzhen (Frontiers in Pharmacology, 2021)
As a newly approved oral hypoglycemic agent, the sodium-glucose co-transporter 2 inhibitor (SGLT2i) dapagliflozin deriving from the natural product phlorizin can effectively reduce blood glucose. Recent clinical studies have found that dapagliflozin alleviates non-alcoholic fatty liver disease (NAFLD), while the specific mechanism remains to be explored. This study aimed to investigate the underlying mechanism of dapagliflozin in alleviating hepatocyte steatosis in vitro and in vivo. We fed the spontaneous type 2 diabetes mellitus rats with high-fat diets and cultured human normal liver LO2 cells and human hepatocellular carcinoma HepG2 cells with sodium palmitate (PA) to induce hepatocellular steatosis. Dapagliflozin attenuated hepatic lipid accumulation both in vitro and in vivo. In ZDF (Zucker Diabetic Fatty) rats, dapagliflozin reduced the hepatic lipid accumulation and acetyl-CoA carboxylase 1 (ACC1) phosphorylation, while upregulated lipid β-oxidation enzyme Acyl-coenzyme A oxidase 1(ACOX1). Further, dapagliflozin increased the expression of autophagy-related markers LC3B and Beclin1, in parallel with a drop in p62 level. These similar effects were observed in PA-stimulated LO2 cells and HepG2 cells. Dapagliflozin treatment could also significantly activated AMPK and reduced phosphorylation of mTOR in ZDF rats and PA-stimulated LO2 cells and HepG2 cells. We demonstrated that dapagliflozin ameliorates hepatic steatosis by decreasing lipogenic enzyme, while inducing fatty acid oxidation enzyme and autophagy, which could be associated with AMPK activation. Moreover, our results indicates that dapagliflozin induces autophagy via the AMPK-mTOR pathway. These findings reveal a novel clinical application and functional mechanism of dapagliflozin in the treatment of NAFLD.